2013
DOI: 10.1590/s0004-27302013000600009
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre consumo de alimentos embutidos e obesidade em um estudo de base populacional de nipo-brasileiros

Abstract: , Japanese-Brazilian Diabetes Study Group 3 RESUMO Objetivo: Investigar a associação entre consumo de alimentos embutidos e obesidade generalizada, abdominal e generalizada com abdominal em nipo-brasileiros de Bauru, SP. Sujeitos e métodos: Quatrocentos e quarenta e três mulheres e 329 homens nipo-brasileiros não miscigenados (≥ 30 anos) foram avaliados em estudo transversal de base populacional. Para o diagnóstico de obesidade, foram empregados os critérios da Organização Mundial da Saúde para asiáticos. A in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
3
0
2
Order By: Relevance
“…These results reinforce results of other studies with Japanese-Brazilians [4, 22]. A study carried out in Bauru with 772 Japanese-Brazilians observes that the intake of fat and processed food were positively associated with obesity in men [19]. Thus, men are probably more vulnerable to risk factors to being overweight, which points to the need to broaden and deepen the gaze on gender differences to support adequate planning for coping and treatment of health conditions associated with excess weight.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results reinforce results of other studies with Japanese-Brazilians [4, 22]. A study carried out in Bauru with 772 Japanese-Brazilians observes that the intake of fat and processed food were positively associated with obesity in men [19]. Thus, men are probably more vulnerable to risk factors to being overweight, which points to the need to broaden and deepen the gaze on gender differences to support adequate planning for coping and treatment of health conditions associated with excess weight.…”
Section: Discussionsupporting
confidence: 88%
“…Japanese-Brazilians are probably included in this scenario as a consequence of Westernization in their life habits [4]; some studies with this specific population [4, 6, 19] report high rates of overweight and obesity corroborating the process of acculturation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, research has shown that chicken intake was not associated with abdominal obesity in men or generalized obesity in both sexes. 27 Also, the study by Ma et al 28 found that salt intake is higher among overweight individuals. A possible explanation for the finding of the present study refers to the reverse causality, commonly found in cross-sectional studies.…”
Section: Discussionmentioning
confidence: 97%
“…The exercise programmes were designed to follow recommended principles of prescription and progression of resistance training for older adults in general and in the aquatic environment [13,42]. Researchers conducting the training sessions will guide the exercise execution with abdominal contraction, spine stabilisation and correction of lower-limb alignment and upright stance.…”
Section: Methodsmentioning
confidence: 99%